2014
DOI: 10.1016/j.indmarman.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The coopetition paradox and tension in coopetition at multiple levels

Abstract: This article explores the nature of the paradox inherent in coopetition; that is, the simultaneous pursuit of cooperation and competition between firms, and emanating tensions that develop at individual, organizational, and inter-organizational levels. We dissect the anatomy of the coopetition paradox to discover how it materializes by creating an external boundary (i.e., via unifying forces) and internal boundaries (i.e., via divergent forces). After explaining the coopetition paradox, we distinguish tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
374
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 359 publications
(393 citation statements)
references
References 50 publications
7
374
0
12
Order By: Relevance
“…On one hand, the uncertainty of the future encourages cooperation in order to acquire benefits [83,100]. On the other hand, coopetitive relationships are characterized by a high level of opportunistic behavior [99], sudden twists [101], tensions [102], the pursuit of private benefits [103], and the short-term horizon of actions [104]. The issue of the time required to generate benefits and costs occurring in particular areas of the value chain then arises.…”
Section: Duration Of Coopetitionmentioning
confidence: 99%
“…On one hand, the uncertainty of the future encourages cooperation in order to acquire benefits [83,100]. On the other hand, coopetitive relationships are characterized by a high level of opportunistic behavior [99], sudden twists [101], tensions [102], the pursuit of private benefits [103], and the short-term horizon of actions [104]. The issue of the time required to generate benefits and costs occurring in particular areas of the value chain then arises.…”
Section: Duration Of Coopetitionmentioning
confidence: 99%
“…However, the slope itself is static because it illustrates the division between dominance in either cooperation or competition. The subject of balanced coopetition is discussed in the literature from the perspective of tension in relationships (e.g., Lado, Boyd, & Hanlon, 1997;Raza-Ullah, Bengtsson, & Kock, 2004;Tidström, 2014). We see balanced coopetition as a state in which the interaction is even in terms of degree of cooperative and competitive activities in the relationship.…”
Section: Coopetition Interactionmentioning
confidence: 99%
“…This addresses the vague and fragmented way in which tensions have been studied and understood to date. As, for example, Raza-Ullah et al (2014) argue, only after tensions have been identified and conceptualized can they be approached and dealt with. In response to the need for an organized framework, a last contribution is our tension-based framework, which brings some essential tension-related pieces together.…”
Section: Introductionmentioning
confidence: 99%